MEMBANGUN KARAKTER GURU MENJADI SMART AND GOOD CITIZEN - ., Kaelan (PKn Progresif, 2012)
Building the character of individuals and nations have a very serious challenge. Various cases of moral decadence, has destroyed the moral personality of individuals and nations. Thus education has a duty and responsibility is very great, especially the teachers in doing character building of students in order to form an smart character and good citizenship are based on local genius